Topologic distributions of vasa vasorum and lymphatic vasa vasorum in the aortic adventitia – Implications for the prevalence of aortic diseases. (April 2016) - Sano, Masaki; Unno, Naoki; Sasaki, Takeshi; Baba, Satoshi; Sugisawa, Ryota; Tanaka, Hiroki; Inuzuka, Kazunori; Yamamoto, Naoto; Sato, Kohji; Konno, Hiroyuki
Abstract: Background and aims: Vasa vasorum (VV) and lymphatic vasa vasorum (LVV) form their own networks in the adventitia. VV supply the aorta with nutrition and oxygen; however, the distribution and role of LVV remains to be determined. The purpose of this study was to investigate differences in the distribution of VV and LVV along the aorta. Methods: Aortic samples were obtained from 22 autopsy cases without medical history of aortic diseases. Aortic segments were classified as arch (Ar), descending thoracic (De), suprarenal abdominal (S-Ab), and infrarenal abdominal (I-Ab). Adventitial VV and LVV were identified immunohistochemically. Results: VV were most dense in the arch aorta, becoming less dense along the aorta in more distal segments, with the lowest density occurring in the infrarenal abdominal aorta. There was a significant correlation between the numbers of VV and medial thickness in the total aortic segments (r = 0.518, p < 0.01). In contrast, there was no significant correlation between the number of LVV and medial thickness in any aortic segments. However, there was a significant correlation between the number of LVV and intimal thickness in I-Ab (r = 0.425, p < 0.05). Conclusions: The distributions of adventitial VV and LVV were characteristic along the aortic segments. Differences in the distributions may imply the prevalence of aortic diseases such as dissection, abdominal aortic aneurysm, and atherosclerotic occlusive disease in each aortic segment. Highlights: This study investigated distributions of arterial vasa vasorum (VV) and lymphatic vasa vasorum (LVV) along the aorta. Unlike VV, LVV density was not correlated with aortic medial thickness. VV were most dense in the arch aorta, becoming less dense along the aorta with the lowest density in the infrarenal aorta. LVV were most dense in the infrarenal aorta and correlated with intimal thickness.